(untitled) (London, 2003)
This invaluable book attempts to bridge business management and scientific management practices so as to foster better understanding between the two entities. It focuses on commercialization of research outcomes. Using cases extensively to illustrate practical difficulties encountered in working across functional barriers, the book also provides guidelines on how these difficulties can be overcome
Keywords: Research, Industrial,New products; Economic aspects,Marketing